Penyediaan Fasiliti dan Tahap Kepuasan Pengguna di Klinik Waqaf An-Nur Masjid Al-Makmur, Taman Bukit Tiram, Ulu Tiram, Johor - Abd Rahman, Siti Zaharah (Research in Management of Technology and Business, 2021)
Waqf is not a strange issue an which for the Muslim property management. Waqf is under the jurisdiction of the State Islamic Religious Council in Malaysia (MAIN). Study indicates that Waqf plays a very important role in the development of the health of a nation. The purpose of this study is to identify issues and challenges in the management of waqf clinics in Johor and to investigate consumer perception of the availability of infrastructure at Klinik Waqaf An-Nur, Masjid Al-Makmur, Taman Bukit Tiram, Ulu Tiram, Johor. This study uses primary and secondary data. The primary data were obtained from a questionnaire conducted at Klinik Waqaf An-Nur, Masjid Al-Makmur, Taman Bukit Tiram. The questionnaire was distributed to 55 respondents. While secondary data from newspaper clippings, books, scientific materials and reading. Interview result shows that the management of the Clinic Waqf An-Nur prioritizes the less fortunate, and the questionnaire indicates that the expectations of Klinik Waqaf An-Nur users in terms of facilities, infrastructure and location and accessibility are at a strong and satisfying.